Fixed low-dose ultrasound-assisted catheter-directed thrombolysis followed by routine stenting of residual stenosis for acute ilio-femoral deep-vein thrombosis - Engelberger, Rolf P.; Fahrni, Jennifer; Willenberg, Torsten; Baumann, Frederic; Spirk, David; Diehm, Nicolas; Do, Dai-Do; Baumgartner, Iris; Kucher, Nils (Thrombosis and Haemostasis, 2014)
Patients with ilio-femoral deep-vein thrombosis (DVT) are at high risk of developing the postthrombotic syndrome (PTS). In comparison to anticoagulation therapy alone, extended venography-guided catheter-directed thrombolysis without routine stenting of venous stenosis in patients with ilio-femoral DVT is associated with an increased risk of bleeding and a moderate reduction of PTS. We performed a prospective single-centre study to investigate safety, patency and incidence of PTS in patients with acute iliofemoral DVT treated with fixed-dose ultrasound-assisted catheter-directed thrombolysis (USAT; 20 mg rt-PA during 15 hours) followed by routing stenting of venous stenosis, defined as residual luminal narrowing >50%, absent antegrade flow, or presence of collateral flow at the site of suspected stenosis. A total of 87 patients (age 46 ± 21 years, 60% women) were included. At 15 hours, thrombolysis success ≥50% was achieved in 67 (77%) patients. Venous stenting (mean 1.9 ± 1.3 stents) was performed in 70 (80%) patients, with the common iliac vein as the most frequent stenting site (83%). One major (1%; 95% CI, 0–6%) and 6 minor bleedings (7%; 95%CI, 3–14%) occurred. Primary and secondary patency rates at 1 year were 87% (95% CI, 74–94%) and 96% (95% CI, 88–99%), respectively. At three months, 88% (95% CI, 78–94%) of patients were free from PTS according to the Villalta scale, with a similar rate at one year (94%, 95% CI, 81–99%). In conclusion, a fixed-dose USAT regimen followed by routine stenting of underlying venous stenosis in patients with iliofemoral DVT was associated with a low bleeding rate, high patency rates, and a low incidence of PTS.
Keywords: Haemorrhage; mechanical thrombolysis; postthrombotic syndrome; vascular patency; venous thrombosis